MMGZ01, an anti-DLL4 monoclonal antibody, promotes nonfunctional vessels and inhibits breast tumor growth. Issue 1 (1st March 2016) - Xu, Zhuobin; Wang, Zegen; Jia, Xuelian; Wang, Luxuan; Chen, Zhiguo; Wang, Shijing; Wang, Min; Zhang, Juan; Wu, Min
Highlights: We generated a novel monoclonal antibody MMGZ01 that specifically binds to DLL4 with high affinity. MMGZ01 disrupted the interaction between DLL4 and Notch1 leading to an increase in nonfunctional vasculature. MMGZ01 inhibited breast tumor growth effectively by multiple mechanisms in vivo. MMGZ01 reduced BCSC population and induced the reversal of EMT either alone or in combination with docetaxel. MMGZ01 provides a new approach for breast cancer therapy. Abstract: Increasing evidence suggests that DLL4 (Delta-like 4)-Notch signaling plays a critical role in cell fate determination and differentiation in tissues. Blocking DLL4-Notch signaling results in inhibition of tumor growth, which is associated with increased nonfunctional vessels and poor perfusion in the tumor. We successfully generated a human DLL4 monoclonal antibody MMGZ01 that binds specifically to DLL4 to disrupt the interaction between DLL4 and Notch1. MMGZ01 showed high affinity to DLL4 to inhibit the DLL4-mediated human umbilical vein endothelial cell (HUVEC) phenotype. Furthermore, MMGZ01 stimulated HUVEC vessel sprouting and tubule formation in vitro. In addition, MMGZ01 had a pronounced effect in promoting immature vessels and reduced breast cancer cell growth in vivo. Finally, MMGZ01 treatment inhibited the proliferation of breast cancer cells, induced tumor cell apoptosis, suppressed mammosphere formation, decreased CD44 + /CD24 − cell population, and reduced epithelial mesenchymal transition (EMT). These findings suggest that antagonism of the DLL4-Notch signaling pathway might provide a potential therapeutic approach for breast cancer treatment.